An enhanced separable reversible and secure patient data hiding algorithm for telemedicine applications. (30th December 2021) - Bhardwaj, Rupali; Aggarwal, Ashutosh
Abstract: In telemedicine industry, a standout among the most significant issues is the exchange of Electronic Patient Information (EPI) between patient and a doctor that are remotely connected. A minute change to EPI may result in wrong diagnosis to the patient. With the aim to ensure secure and safe communications in telemedicine framework, an enhanced separable reversible data hiding technique in encrypted domain has been presented here that gives high embedding rate by embedding k, ( k ≥ 1 ) binary bits of patient data in b a s e 2 k numeral framework using Average Pixel Repetition (APR) method. APR method converts original image of size M × N into encrypted scaled-up image of size ( 2 × M − 1 ) × ( 2 × N − 1 ) such that non-seed pixels are used for data embedding where as seed pixels remain as it is to facilitate reversibility. The experimental study shown that the proposed method gave extremely high embedding rates on both natural and medical images. For all test images, the proposed methodology altogether beated all the compared methodologies in its ability to embed patient information and precisely recover it with maintaining the visual quality of stego images too. Highlights: APR based scaled-up image generation to facilitate reversibility. Data is embedded with the help of weighted pixel geometry matrix. Less computational complexity with high payload and separable reversibility feature. Security and authentication analysis of secret message is performed.